Time Allocation in Rural Households : The Indirect Effects of Conditional Cash Transfer Programs - Hasan, Amer (2012)
Conditional cash transfers are being heralded as effective tools against the intergenerational transmission of poverty. There is substantial evidence on the positive effects of these transfers. Analysts are only now beginning to investigate the indirect effects these programs generate. This paper examines the effect of a gender-targeted conditional cash transfer program on the time allocation of mothers in rural program-eligible households. Using a fixed effects difference-in-differences estimator, the author finds that program eligibility is associated with an increase of 120 minutes of housework per typical school day by mothers of eligible children in the stipend district when compared with mothers of eligible children in the non-stipend district. There is a 100-minute reduction in the amount of time mothers report spending on children s needs. The intent-to-treat effect of the program suggests no change in the amount of time spent on paid work or sleep.